EFEKTIVITAS EKSTRAK DAUN KELOR (Moringa oleifera Lamk) DENGAN KONSENTRASI YANG BERBEDA TERHADAP KADAR AIR DAN KADAR PROTEIN TELUR ITIK ASIN - Fatrah, M. Fachri; Novieta, Intan Dwi; Irmayani, I. (bionature, 2019)
ABSTRACT M. FACHRI FATRAH (NIM. 1215140054). The level of effectiveness of Moringa leaf’s extract (Moringa oleifera lamk) with different concentrations to moisture degree and protein degree of salted duck egg, (guided by Intan Dwi Novieta and Irmayani).The aim of this study is to know the influence of Moringa leaf’s extract (Moringa oleifera Lamk) towards moisture degree and protein degree of salted duck egg. This study use completely randomized design (CRD) with 4 treatments level and 3 replications i.e. K0= without moringa leaf’s extract 0%, K1= addition of moringa leaf’s extract 10%, K2= addition of moringa leaf’s extract 20%, K3= addition of Moringa leaf’s extract 30%.The result of the study showed that by addition of moringa leaf’s extract treatment with difference concentration give a real influence (P<0,01) towards moisture degree and rough protein degree of salted duck egg. The average value of the lowest to the highest moisture degree i.e. K0 (35,67%), K2 (36,36%), K1 (38,47%)  and K3 (39,58%). The average value of the highest to the lowest rough protein degree i.e. K0 (20,60%), K2 (19,69%), K3 (19,47%) and K1 (18,98%). Based on the result of the study then the best treatment and can be recommended is the treatment K2 with 20% moringa leaf’s extract  addition.Keywords:     Moringa Leaf’s Extract, Salted Duck Egg, Moisture Degree, Protein Degree